AB1077 Does preconsult electronic exchange affect postconsult diagnosis?. (15th June 2017) - Miller, G; Chou, B; Patel, N; Karpouzas, G
Abstract : Background: Harbor UCLA is an urban safety-net hospital in Los Angeles for underserved patients. In 2014, LA County Department of Health Services adopted an electronic consultation (E-consult) referral and dialogue system to improve access to subspecialists in the ambulatory care setting. The E-Consult system provides a platform for primary care providers to ask questions or engage in dialogue with specialists, request consultation, and track submitted requests. Back and forth messaging prior to acceptance for face-to-face consultation is termed a "preconsult exchange". Prior studies of E-Consult systems have suggested benefits which include a reduction in wait times compared to paper referrals 1 and a perceived improvement in patient care 2 . We sought to further clarify the effect of a preconsult exchange versus immediate booking on a patient's diagnosis and wait time in an effort to provide some guidance on whether E-Consult should be used as a screening tool to reduce unnecessary visits or as a communication method to clarify details before a face-to-face visit. Objectives: To determine whether preconsult exchange: 1. Influences the odds of arriving at a different diagnosis after face-to-face consultation compared to the requesting provider's original diagnosis 2. Influences the odds of arriving at a diagnosis of a different autoimmune condition versus a non-autoimmune condition (fibromyalgia, primary osteoarthritis, chronic pain, or other non-rheumatologic condition) 3. Results in a significant delay in face-to-face evaluation Methods: We performed a retrospective chart review of all 238 new patient referrals between 11/2014 and 5/2016 to the Harbor UCLA Rheumatology clinic generated through the E-Consult system, reviewed by BC or GM, deemed appropriate, and seen for face-to-face evaluation. These patients were grouped by exposure (Preconsult exchange or not). Odds of change in diagnosis and confidence intervals were calculated using 2x2 contingency tables and Chi-Square tests. A student's T test was used to compare mean number of days between E-Consult initiation and face-to-face appointment. Conclusions: There was a trend towards a change in diagnosis overall among patients for whom there was a preconsult exchange, but a statistically significant increase in odds for change to non-immunologic diagnoses. This suggests that preconsult exchange highlights those patients for whom there is a higher likelihood of a non-immunologic diagnosis. However, preconsult exchange was associated with a significant time cost - an additional 26 day delay for a face-to-face visit (due to the time needed for both submitter and reviewer to complete their dialogue) in comparison to an immediately booked patient. References: Chen A et al. A Safety-Net System Gains Efficiencies Through 'eReferrals' To Specialists. Health Affairs 29, no.5 (2010):969–971. Scheibe MM et al. Efficiency Gains for Rheumatology Consultation Using a Novel Electronic Referral System in a Safety-Net Health Setting. Arthritis Care Res (Hoboken). 2015 Aug;67(8):1158–63. Disclosure of Interest: None declared